IARC 2019: “Night shift work” is probably carcinogenic: What about disturbed chronobiology in all walks of life? - Erren, Thomas C. (J Occup Med Toxicol, 2019)
In June of 2019, a working group convened by the International Agency for Research on Cancer [IARC] concluded that “night shift work” is probably carcinogenic to humans (a Group 2A carcinogen). This was based on sufficient evidence of cancer and strong mechanistic evidence in experimental animals and limited evidence from human epidemiological studies. The biological basis from experimental work is clear and compelling: Disturbed chronobiology such as due to alterations in the light-dark schedule which shift-workers experience is associated with carcinogenicity. But is it correct to assume in epidemiological studies that “night shift work” provides the same dose of disturbed chronobiology to all night workers and that disturbed chronobiology from activities outside of work does not count? Both chronobiological theory and supporting evidence suggest that much-needed future epidemiology should address these questions and should consider disturbed chronobiology in all walks of life.